ANALISIS PENGARUH PELAYANAN, HARGA, DAN PRODUK TERIIADAP KEPUASAN DEBITUR PT BANK NEGARA INDONESIA (PERSERO) TBK. UNIT KREDIT KECIL PURWOREJO - , Febry Normadian ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to examine: (1) the influence of service on debtorâs satisfaction in PT. Bank Negara Indonesia (Persero) Tbk. Purworejo Small Credit Unit, (2) the influence of price on debtorâs satisfaction in PT. Bank Negara Indonesia (Persero) Tbk. Purworejo Small Credit Unit, dan (3) the influence of product on debtorâs satisfaction in PT. Bank Negara Indonesia (Persero) Tbk. Purworejo Small Credit Unit. Samples are taken from 116 respondents who are debtors of Micro Small Medium Enterprise in PT. Bank Negara Indonesia (Persero) Tbk. Purworejo Small Credit Unit. Sampling method use nonprobability with quota unproportional sampling. Primary data obtained through a questionnaire using Likert Scale. Analytical techniques used in this study is multiple regression analysis. The results shows that the service, price, and product have a positive significant impact to debtorâs satisfaction in PT. Bank Negara Indonesia (Persero) Tbk. Purworejo Small Credit Unit. Price became the most dominant factor affecting the debtorâs satisfaction with the Î² value of 0,401, while the service becomes the lowest impact factor on debtorâs satisfaction with the Î² value of 0,096. Product have an impact to debtorâs satisfaction with the Î² value of 0,291.